TERRORISM CRIMES IN INDONESIA: A COUNTERTERRORISM PERSPECTIVE - Muhammad Hatta; Ramalinggam Rajamanickam; Tengku Noor Azira Tengku Zainudin; Mohd Zamre Mohd Zahir; Zulfan; Husni (Malaysian Journal of Syariah and Law)
Terrorism has emerged as a significant concern in contemporary societies. In Indonesia, the primary factor contributing to individual involvement in terrorism is the pervasive influence of deviant Islamic ideologies, particularly those pertaining to jihad and caliphate governance. Misinterpretations of Islamic teachings, with an inclination towards extremism, substantially increase an individual's propensity to engage in terrorist acts such as suicide bombings. This study aimed to investigate terrorism in Indonesia using an anti-terrorism approach, specifically counter radicalism. This qualitative research employed normative or doctrinal methodologies to identify, explain, analyse, and systematically articulate facts, principles, concepts, theories, and laws, with the objective of generating new knowledge and ideas for legal reform. It is crucial to acknowledge that the motivations of terrorist groups in Indonesia extend beyond religious doctrine. These groups sought to fully implement Islamic law (kaffah) and establish an Islamic state (Darul Islam) through the caliphate system. Associated with the Islamic State of Iraq and Syria (ISIS), these entities aimed to establish both an Islamic state within Indonesia and a global Islamic caliphate. The Indonesian government can enhance its counterterrorism initiatives by implementing more stringent penalties for those involved, as delineated in Law No. 5 of 2018, which focuses on eradicating terrorism. Furthermore, the government should augment proactive measures by instituting a counterterrorist ideological programme to cultivate a comprehensive understanding of Islamic teachings and national values, thereby ensuring accurate comprehension among individuals. The study concluded that terrorist organisations in Indonesia are motivated not only by religious fanaticism, aimed at the perfect implementation of Islamic law (kaffah), but also by political ambitions to establish an Islamic state (Darul Islam) within the country. This study is expected to enhance the comprehensive understanding of the implementation of counter-ideological and de-radicalization initiatives while also promoting nationalist values to preserve the integrity of the Republic of Indonesia.